1995
DOI: 10.1007/bf00207375
|View full text |Cite
|
Sign up to set email alerts
|

Screening for naturally occurring apolipoprotein A-I variants: apo A-I(?K107) is associated with low HDL-cholesterol levels in men but not in women

Abstract: Isoelectric focussing (IEF) in carrier ampholyte-generated pH gradients and hybrid isoelectric focussing (HIEF) in immobilized pH gradients under nondenaturing conditions were used in parallel to screen 5,500 plasma samples for naturally occurring variants of apolipoprotein A-I (apo A-I). The following defects were identified in four unrelated subjects heterozygous for apo A-I variants: apo A-I(delta K107)(2 x), apo A-I(K107M)(1 x), and apo A-I(E41R)(1 x). The later variant is a novel finding. Family studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Similar reductions have been described for other apoA-I mutations (23,24) although some reports describe HDL-C reductions up to 80% of normal (24). Finally, we noted no effects on TG levels, which is in contrast with a study that revealed higher TG levels in men suffering from an other apoA-I (delta K107) defect (25). ApoA-I (L178P): cardiovascular disease.…”
Section: Apoa-i (L178p): Effects On Apoa-i Levels Hdl Cholesterol Asupporting
confidence: 73%
“…Similar reductions have been described for other apoA-I mutations (23,24) although some reports describe HDL-C reductions up to 80% of normal (24). Finally, we noted no effects on TG levels, which is in contrast with a study that revealed higher TG levels in men suffering from an other apoA-I (delta K107) defect (25). ApoA-I (L178P): cardiovascular disease.…”
Section: Apoa-i (L178p): Effects On Apoa-i Levels Hdl Cholesterol Asupporting
confidence: 73%
“…The apoA-I[K107del] variant is found in Caucasian and Asian populations and is the most frequent apoA-I variant in the population of Germany (1:5,000) ( 13,19 ). It is associated with HTG, hypoalphacholesterolemia, and amyloidosis ( 12,13,19,20 ).…”
Section: Preparation Of Tg-rich Emulsion Particlesmentioning
confidence: 99%
“…It is associated with HTG, hypoalphacholesterolemia, and amyloidosis ( 12,13,19,20 ). Several groups have investigated the properties of the apoA-I[K107del] in order to clarify the molecular mechanisms underlying the development of the hypoalphacholesterolemia in carriers of this variant.…”
Section: Preparation Of Tg-rich Emulsion Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 for the two apolipoproteins having the highest number of naturally occurring mutations reported thus far (30)(31)(32)(33)(34)(35)(36), it is then evident that such mutations do spare the "Y, L/I/V/M, X, X, V/L/I" motif and immediately adjacent residues, but not other functional domains. I therefore conclude that evolution dictated that preservation of the chemical integrity of the core (ie, the 5-residue motif) of the thyroid hormone binding domain is much more important than preservation of other binding sites or (sub-)domains, to such a point that its alteration could be lethal.…”
Section: Discussionmentioning
confidence: 95%